2022
DOI: 10.1021/acssensors.1c02388
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Monitoring of Ammonia Using an MXene/TiO2/Cellulose Nanofiber Heterojunction-Based Sensor Driven by an Electrospun Triboelectric Nanogenerator

Abstract: Real-time monitoring of harmful gases is of great significance to identify the environmental hazards to people's lives. However, this application scenario requiring low-power consumption, superior sensitivity, portability, and self-driven operation of gas sensors remains a challenge. Herein, an electrospun triboelectric nanogenerator (TENG) is synthesized using highly electronegative and conducting MXene nanofibers (NFs) paired with biodegradable cellulose acetate NFs (CA-NFs) as triboelectric layers, which su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(74 citation statements)
references
References 52 publications
(72 reference statements)
1
73
0
Order By: Relevance
“…This is due to the limited ammonia‐sensitive functional groups on the surface of Ti 3 C 2 T x as the cycle time and the number of cycles increase, the reaction of the gas with the surface of the frictional electric material gradually decreases, and eventually, the sensitivity of the sensor should gradually decrease with the surface reaction with the gas (Figure S7 , Supporting Information). [ 33 ] The response values shown in Figure 5j indicate that the PFOTES‐Ti 3 C 2 T x ‐CNF has great sensitivity to ammonia gas at the same gas concentrations, which is considered for the formation of more adsorption sites on the PFOTES‐Ti 3 C 2 T x ‐CNF film. [ 34 ] The 2D structure of Ti 3 C 2 T x gives it a higher specific surface area and can adsorb many end‐joining groups on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the limited ammonia‐sensitive functional groups on the surface of Ti 3 C 2 T x as the cycle time and the number of cycles increase, the reaction of the gas with the surface of the frictional electric material gradually decreases, and eventually, the sensitivity of the sensor should gradually decrease with the surface reaction with the gas (Figure S7 , Supporting Information). [ 33 ] The response values shown in Figure 5j indicate that the PFOTES‐Ti 3 C 2 T x ‐CNF has great sensitivity to ammonia gas at the same gas concentrations, which is considered for the formation of more adsorption sites on the PFOTES‐Ti 3 C 2 T x ‐CNF film. [ 34 ] The 2D structure of Ti 3 C 2 T x gives it a higher specific surface area and can adsorb many end‐joining groups on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…[200] Furthermore, the inclusion of nanotriboelectric generators in chemiresistor circuitry results in their selfoperation without using any external power source. For instance, Sardana et al [201] reported selfdriven room tem perature ammonia detecting chemiresistor based on MXene/ TiO 2 /Cellulose nanofiber heterojunction driven using electro spunbased triboelectric nanogenerators. The chemiresistor demonstrated high sensitivity, selectivity and reproducibility with rapid response and recovery within 76 and 32 s. The work opened a new window to architect intelligent and realtime gas leakage detection by selfdriven and sustainable chemiresistor powered by human motion.…”
Section: Cutting-edge Prospectsmentioning
confidence: 99%
“…The gas sensor exhibited great reproducibility and high selectivity. [ 128 ] Figure a depicts the possible mechanism of MXene/TiO 2 /C‐NFs heterojunction‐based sensor and the electron transfer process between MXene and TiO 2 . The electrons of n‐type TiO 2 gradually migrate into the conduction band of MXene until the Fermi levels of the two materials flatten.…”
Section: Self‐powered Teng/peng Sensors Based On Various 2d Materialsmentioning
confidence: 99%
“…Reproduced with permission. [ 128 ] Copyright 2022, American Chemical Society. b) Fabrication process and schematic structure of a Si/n‐CdS NWs heterostructure near‐infrared photodetector.…”
Section: Self‐powered Teng/peng Sensors Based On Various 2d Materialsmentioning
confidence: 99%